Feasibility of home-based transcranial direct current stimulation combined with personalized word retrieval for improving naming in primary progressive aphasia - Allan George; Eric McConathey; Amy Vogel-Eyny; Elizabeth Galletta; Giuseppina Pilloni; Leigh Charvet (Frontiers in Neurology)
Background/ObjectivesPrimary progressive aphasia (PPA) is managed with speech-language therapy (SLT) to slow language decline. Pairing transcranial direct current stimulation (tDCS) with SLT can enhance its effects. However, further research is needed to confirm these findings and guide its clinical use. We evaluated the feasibility of providing an intervention combining tDCS with SLT as a home-based and remotely supervised intervention.MethodsParticipants with confirmed PPA who had word-finding difficulties were recruited for an open-label observational study. The intervention consisted of 20 daily sessions over 1 month, each with 45-min of personalized word retrieval training. During the first 30-min, participants received tDCS over the left inferior frontal gyrus (anode F7, cathode O1) at 2.0 mA. Language measures were remotely administered at baseline and intervention end.ResultsWe enrolled 10 patients (age: 70 ± 7 years; 60% male) with confirmed logopenic variant (n = 2), semantic variant (n = 2), or unspecified (n = 6) PPA. The intervention was well-tolerated with no treatment-limiting adverse events. All participants completed all sessions, confirming the feasibility of the home-based treatment. There were no declines in language functioning measures, with improved naming for trained vs. untrained items (p = 0.003) and a significant improvement in confrontation naming (p = 0.016) from baseline to intervention end.ConclusionsOur case series demonstrates that home-based tDCS added to SLT is feasible for patients with PPA. However, larger controlled studies are required to confirm its effectiveness in slowing language decline and to fully determine the benefits of this approach. This approach not only facilitates broader access to participation but also enables the extended treatment necessary to evaluate its clinical benefits, moving this treatment closer to clinical availability as a telehealth treatment.